2017
DOI: 10.1080/17482631.2017.1333898
|View full text |Cite
|
Sign up to set email alerts
|

Arts as an ecological method to enhance quality of work experience of healthcare staff: a phenomenological-hermeneutic study

Abstract: This paper explores the impact of self-chosen arts-based recreational activities, as opposed to the traditional arts therapy activities, on the well-being of healthcare providers. Three qualitative case studies of programs in which arts-based activities were used to work with healthcare providers, lasting for 10 weeks each, are phenomenological-hermeneutically evaluated using interviews and focus groups. The findings show what we refer to as an “ecological” ripple of effects: (1) the arts-based activities help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Specialized training should be guaranteed in order to enhance interpersonal, emotional, and social competences in healthcare staff [ 34 , 81 ]. Participation in arts-based activities for example has been proved to exert effects on different levels, such as psychological, emotional, and social [ 82 ]. Professionals should be supported not only in facing typical and widespread burnout symptoms, but also to cope with cultural and social rapid transformations which often suggest new and different ways of working.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized training should be guaranteed in order to enhance interpersonal, emotional, and social competences in healthcare staff [ 34 , 81 ]. Participation in arts-based activities for example has been proved to exert effects on different levels, such as psychological, emotional, and social [ 82 ]. Professionals should be supported not only in facing typical and widespread burnout symptoms, but also to cope with cultural and social rapid transformations which often suggest new and different ways of working.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative results. Finally, three studies (i.e., Horwitz et al, 2017;Pearce, 2017;van Westrhenen & Fritz, 2012) examined integrative arts interventions which covered a range of arts domains such as visual arts, dance/movement, singing, creative writing, and drama. The goals and content of the interventions were diverse; however, the two most common PF outcomes that were found in all three studies were relaxation and stress relief and sense of community and belonging.…”
Section: Integrative Interventionsmentioning
confidence: 99%
“…Participants of two studies also reported several negative experiences in participating in these interventions. While the CP program provided participants with relaxing effects, they also generated stress and added burden in trying to implement the program (Horwitz et al, 2017). In the community-based adult creative arts education class (Pearce, 2017), some participants reported having a negative view toward themselves compared with their expectations or their classmates and perceiving themselves as isolated and separate from other participants in the class groups.…”
Section: Integrative Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The arts create metabolic arousal that mobilizes the organism. Indeed, the arts, from a neurobiological perspective, are a way to group together stimuli into a coherent gestalt or unit and, thus, to organize what one wants to communicate to others (Bojner Horowitz et al, 2017; Conway & Pleydell-Pearce, 2000; Sarid & Huss, 2011). On a community level, this process helps to select and update images and sensations that are momentarily most relevant to the individual, and these images become the base of narratives, rituals, symbols, sports, and other forms of symbolic interaction.…”
mentioning
confidence: 99%